The Negative Affect Hypothesis of Noise Sensitivity - Shepherd, Daniel (Int J Environ Res Public Health, 2015)
Some studies indicate that noise sensitivity is explained by negative affect, a dispositional tendency to negatively evaluate situations and the self. Individuals high in such traits may report a greater sensitivity to other sensory stimuli, such as smell, bright light and pain. However, research investigating the relationship between noise sensitivity and sensitivity to stimuli associated with other sensory modalities has not always supported the notion of a common underlying trait, such as negative affect, driving them. Additionally, other explanations of noise sensitivity based on cognitive processes have existed in the clinical literature for over 50 years. Here, we report on secondary analyses of pre-existing laboratory (n = 74) and epidemiological (n = 1005) data focusing on the relationship between noise sensitivity to and annoyance with a variety of olfactory-related stimuli. In the first study a correlational design examined the relationships between noise sensitivity, noise annoyance, and perceptual ratings of 16 odors. The second study sought differences between mean noise and air pollution annoyance scores across noise sensitivity categories. Results from both analyses failed to support the notion that, by itself, negative affectivity explains sensitivity to noise.